AGE SPAN FORMATION IN GRANITOIDS OF UKRAINIAN SHIELD - Stepanyuk, L.; Hrinchenko, O.; Dovbush, T.; Ziultsle, O.; Konoval, N.; Mironchuk, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper discusses Berdychiv type granitoids that have always stirred up interest among researchers of the Ukrainian Shield. These rocks include minerals that are uncharacteristic of granites - cordierite, sillimanite, andalusite - and are closely related to rocks of the supposed substratum. At the same time, there still remain questions about the genetic nature of Berdychiv granites. Despite the fact that most researchers treat these granites as intrusive (anatectic) formations, there are other concepts according to which these granites are considered to be the products of metasomatic transformation (magmatic replacement) of primarily argillaceous and marly series of substratum. The Stryzhavka open pit, which is located in the Upper Bug region of the Ukrainian Shield displays differently cataclised porphyry-like plagiogranitoids (predominantly, garnet-bearing varieties in its southwestern area, locally rock-forming potassic feldspar varieties), and garnet-bearing leucocratic granites similar to those of Berdychiv type granites. The monazites of biotite-garnet granodiorite and biotite-garnet granite were dated by uranium-lead (U-Pb) isotopic dating method. The monazite of granodioritеs is dated 2049,3±3,5 million years based on the upper intersection of concordia with discordia. Significantly lower values of age (about 15 million years younger) for the monazite selected from granite, approximating 2035,1±1,9 million years were established. We assume it to be caused by prolonged crystallization of granitic melt and rather early crystallization of more basiс granodioritic magma in comparison with granitic one. Thus, the duration of the granitoid formation uncovered in the Stryzhavka open pit exceeds 15 million years, which correlates accurately with the estimates for occurrence duration of the granitic melts, which gave rise to various granites of the Ukrainian Shield.